Water retention curve of coconut fiber substrate for cultivation in pots in greenhouse - Nascimento, Erlen Kaline Ávila do; Rego, Lunara Gleika da Silva; Miranda, Neyton de Oliveira; Figueirêdo, Vladimir Batista; Silva, Nathalia Gomes (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
A substrate with adequate porosity and water retention capacity makes it possible to maximize the yield and quality of crops produced in containers in greenhouses. A great alternative is coconut fiber, which needs careful irrigation management, which can be based on monitoring the water content in the root zone using tensiometers. In this sense, this work aimed to determine the water retention curve of coconut fiber in pots through the technique of water removal by evaporation and measurement of water tension with tensiometers, after which the pots were weighed and the corresponding water content was calculated by difference between the measured mass and the dry substrate mass. A data acquisition system was used to record the readings from the tensiometer pressure transducers. Tension, water amount and substrate density data were used to fit the water retention curves according to regression models and the Van Genuchten model. The use of tensiometers in the coconut fiber substrate made it possible to determine the water retention curve quickly and practically from almost continuous tension readings between 12 and 268 hPa, corresponding to water contents between 0.37 and 0.05 cm3 cm-3. Thus, it was possible to adjust the retention curve in a simple way, using regression models with high coefficients of determination. Although the hydric parameters of the substrate are lower than those referred to in the literature, they are useful to adequately manage irrigation in containers.